Development of the ACTIVE framework to describe stakeholder involvement in systematic reviews. Issue 4 (October 2019) - Pollock, Alex; Campbell, Pauline; Struthers, Caroline; Synnot, Anneliese; Nunn, Jack; Hill, Sophie; Goodare, Heather; Morris, Jacqui; Watts, Chris; Morley, Richard
Objectives: Involvement of patients, health professionals, and the wider public ('stakeholders') is seen to be beneficial to the quality, relevance and impact of research and may enhance the usefulness and uptake of systematic reviews. However, there is a lack of evidence and resources to guide researchers in how to actively involve stakeholders in systematic reviews. In this paper, we report the development of the ACTIVE framework to describe how stakeholders are involved in systematic reviews. Methods: We developed a framework using methods previously described in the development of conceptual frameworks relating to other areas of public involvement, including: literature searching, data extraction, analysis, and categorization. A draft ACTIVE framework was developed and then refined after presentation at a conference workshop, before being applied to a subset of 32 systematic reviews. Data extracted from these systematic reviews, identified in a systematic scoping review, were categorized against pre-defined constructs, including: who was involved, how stakeholders were recruited, the mode of involvement, at what stage there was involvement and the level of control or influence. Results: The final ACTIVE framework described whether patients, carers and/or families, and/or other stakeholders (including health professionals, health decision makers and funders) were involved. We defined: recruitment as either open or closed; the approach to involvement as either one-time, continuous or combined; and the method of involvement as either direct or indirect. The stage of involvement in reviews was defined using the Cochrane Ecosystem stages of a review. The level of control or influence was defined according to the roles and activities of stakeholders in the review process, and described as the ACTIVE continuum of involvement. Conclusions: The ACTIVE framework provides a structure with which to describe key components of stakeholder involvement within a systematic review, and we have used this to summarize how stakeholders have been involved in a subset of varied systematic reviews. The ACTIVE continuum of involvement provides a new model that uses tasks and roles to detail the level of stakeholder involvement. This work has contributed to the development of learning resources aimed at supporting systematic review authors and editors to involve stakeholders in their systematic reviews. The ACTIVE framework may support the decision-making of systematic review authors in planning how to involve stakeholders in future reviews.